1998
DOI: 10.1017/s002221510014160x
|View full text |Cite
|
Sign up to set email alerts
|

Epithelial atypia and squamous metaplasia in nasal polyps

Abstract: Fifteen routine nasal polypectomy specimens submitted to our laboratory over an eight-month period were noted to show marked atypia within areas of squamous metaplasia to a degree suggestive of dysplasia. Reviewing the literature revealed little published work in this area, especially recently. Further nasal polyp cases from this, and a similar previous time period, were re-examined, and possible causes for these changes discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 4 publications
1
9
0
Order By: Relevance
“…Baird et al 15 in a study of 20 cases of nasal polyps found that 50% of the lesions showed squamous metaplasia and 15% showed atypical changes in the lining mucosal membrane. They concluded that squamous metaplasia was much commoner than previously thought.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Baird et al 15 in a study of 20 cases of nasal polyps found that 50% of the lesions showed squamous metaplasia and 15% showed atypical changes in the lining mucosal membrane. They concluded that squamous metaplasia was much commoner than previously thought.…”
Section: Resultsmentioning
confidence: 99%
“…Baird et al 15 . in a study of 20 cases of nasal polyps found that 50% of the lesions showed squamous metaplasia and 15% showed atypical changes in the lining mucosal membrane.…”
Section: Discussionmentioning
confidence: 98%
“…Baird et al, in a short period of time such as eight months, showed the existence of atypia in fi ft een nasal polypectomy specimens containing squamous metaplasia (22). Th e study shows that preoperative complaint period of patients with metaplasia is longer than those without metaplasia.…”
Section: Discussionmentioning
confidence: 95%
“…20 One unexpected finding in this study was squamous metaplasia in two specimens in the control group. A study by Baird et al 21 of 20 patients with nasal polyps found that 50% showed squamous metaplasia. They attributed this finding to chronicity of the disease.…”
Section: Discussionmentioning
confidence: 98%